Age, growth, and reproductive biology of the five-lined snapper Lutjanus quinquelineatus around Okinawa-jima Island, southern Japan - Araki, Katsuya; Tachihara, Katsunori (Fisheries science, 2021)
The age, growth, and reproductive biology of the five-lined snapper Lutjanus quinquelineatus was estimated using 709 specimens (44.2–197.7 mm) collected from November 2012 to November 2014 around Okinawa-jima Island, southern Japan. The oldest age estimated by sectioned otoliths and maximum standard length were 24 years and 192.1 mm for females and 27 years and 197.7 mm for males. The relationship between age and standard length was expressed by the following von Bertalanffy growth equations; female: L t = 172.2 × {1 − exp[−0.55( t + 0.70)]}; male: L t = 182.5 × {1 − exp[−0.52( t + 0.70)]}. The spawning season estimated by the gonadosomatic index and histological observations was from May to September, with a peak season from June to August. The length (age) at first maturity was 130.3 mm (2 years) for females and 129.5 mm (1 year) for males. Among the small Lutjanus species, L. quinquelineatus has a long lifespan and matures at a small size and young age.